The Ethics Liaison Program: building a moral community. Issue 9 (1st December 2016) - Bates, Sarah R; McHugh, Wendy J; Carbo, Alexander R; O'Neill, Stephen F; Forrow, Lachlan
Abstract : Ethicists often struggle to maintain institution-wide awareness of and commitment to medical ethics. At Beth Israel Deaconess Medical Center (BIDMC), we created the Ethics Liaison Program to address that challenge by making ethics part of the moral culture of the institution. Liaisons represent clinical and non-clinical areas throughout the medical centre. The liaison has a four-part role: to spread awareness and understanding of Ethics Programs among their coworkers; share information regarding ethical dilemmas in their work area with the members of the Ethics Support Service; review ethics activities and needs within their area; and undertake ethics-related projects. This paper lists the notable attributes of the Ethics Liaison Program, and describes the purpose and structure of the programme, its advantages and the challenges to implementing it. The Ethics Liaison Program has helped to make ethics part of the everyday culture at BIDMC, and other medical centres might benefit from the establishment of similar programmes.